2007
DOI: 10.1007/s00586-007-0553-1
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of activities of daily living accompanying reduced neck mobility after laminoplasty preserving or reattaching the semispinalis cervicis into axis

Abstract: Although difficulties with neck mobility often interfere with patients' activities of daily living (ADL) after cervical laminoplasty, there was no detailed study on the relation between the limitations of ADL accompanying postoperative reduced neck mobility and the cervical posterior approach. The aim of this study was to compare retrospectively the frequency of limitations of ADL accompanying neck mobility after laminoplasty preserving the semispinalis cervicis inserted into the C2 spinous process with that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In addition, modified surgical techniques have been developed to preserve the paraspinal muscles, not only to maintain cervical ROM, but also to reduce axial symptoms [11,12]. Roselli et al [12] reported well-preserved cervical ROM after open-door laminoplasty using unilateral muscle dissection, while Takeuchi et al [11,13] maintained cervical ROM following double-door laminoplasty by preserving the semispinalis cervicis inserted into C2. Because bilateral muscle dissection is inevitable during double-door laminoplasty, further modifications to the surgical techniques are desirable to preserve the integrity of the cervical muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, modified surgical techniques have been developed to preserve the paraspinal muscles, not only to maintain cervical ROM, but also to reduce axial symptoms [11,12]. Roselli et al [12] reported well-preserved cervical ROM after open-door laminoplasty using unilateral muscle dissection, while Takeuchi et al [11,13] maintained cervical ROM following double-door laminoplasty by preserving the semispinalis cervicis inserted into C2. Because bilateral muscle dissection is inevitable during double-door laminoplasty, further modifications to the surgical techniques are desirable to preserve the integrity of the cervical muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased excursive ROM, 2,9,25,39,40,52 cervical malalignment, 3,5,16,18,37 late exacerbation of myelopathy symptoms, 19,25,40 and axial neck pain are postoperative problems associated with laminoplasty. 2,5,22,23,25,37,39,43,46 Axial neck pain greatly reduces patient satisfaction with the procedure. 13,24,45 Moreover, decreased lordotic curvature and kyphosis, which involve the semispinalis cervi-A less-invasive cervical laminoplasty for spondylotic myelopathy that preserves the semispinalis cervicis muscles and nuchal ligament Object.…”
mentioning
confidence: 99%
“…The source of neck may be due to many varying pathologies such as whiplash, poor posture, degenerative disorders, neuropathy, tumors, surgical procedures and over working of neck muscles due to faulty postures [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%